Studying the Influencing Factors in the Occurrence of Metabolic Diseases in Cows - Olfat, Ghulamhaidar (Journal of Natural Sciences – Kabul University, 2023)
Metabolic disorders in cattle are a group of diseases that primarily affect dairy cows immediately after parturition. Dairy cattle require minerals in their diet for optimal productivity, which are obtained from feed and fodder. The intake of minerals through feed and water must balance their output through feces, urine, and milk to maintain animal health. If output exceeds intake, animals compensate for short periods by mobilizing body reserves. However, prolonged imbalances lead to productivity-related problems. This study aims to review several factors, such as breed, age, season, environment, and body condition, that contribute to the occurrence of metabolic diseases in cows.